PENGARUH PENGGUNAAN METODE “SENIMAN ALAM” TERHADAP HASIL BELAJAR PADA PEMBELAJARAN TEMATIK INTEGRATIF SISWA SEKOLAH DASAR - Fauzatul Ma'rufah Rohmanurmeta (Profesi Pendidikan Dasar, 2018)
This study aims to determine the effect of natural artist methods on learning outcomes on integrative thematic learning in fourth grade students of elementary school. The research design used in this research is True Experimental form Posttest-Only Control Design. The experimental group of this research is the fourth grader of SDN 1 Nglayang, while the control group is SDN 2 Nglayang. Data collection is done by using the techniques of documentation, tests, and observation. In analyzing the data, this study uses statistical data analysis with the formula t test separated variance. The results of the study showed a significant difference, for dk 4 and significance level of 0.05 obtained t value = 3.296 and t table = 1.7011. The average score of students taught by Natural Artist's learning method is 66.67, while the average score of students taught by conventional learning method is 52. Thus, the use of artist learning method influences the learning outcomes in integrative thematic learning of fourth grade students of SD.